Skogsentreprenad idag och i framtiden : en kvalitativ studie av skogsmaskinentreprenörersverksamhet och framtidsvisioner - Hultåker, Oscar (SLU/Dept. of Forest Products, 2002)
The Department of Forest Products and Management, Swedish University of Agricultural Sciences has received means from Vinnova for a preliminary study of the organisation of logging work of today and how a better logging organisation should be brought about. This thesis reports results from qualitative interviews with nine forest machine contractors regarding the situation of their companies. The interviews have been analysed with respect to the genesis of the companies, which tasks they perform or that they could consider perform-ing, business relationships of the companies, relationships between the different partners of the companies, and the state of competition experienced by the contractors. The companies have developed either from the contractor previously being machine operator employee or from that the contractor in making has owned a machine and needed work. Their primary business is mechanised logging. Complementary services offered by the companies include timber dealing, machine service, planning of logging and other preparations, and complementary manual felling. Furthermore, some contractors carry out nature conservation planning, mechanised silviculture, long-term logging planning, transports, co-ordination work for customers and sub contractors, and developing of administrative IT systems. In the future the forest contractors could think of expanding their business with lorry trans-ports, soil scarification, planning, and assuming a greater overall responsibility for the in-dustry's wood supply. Some of the contractors would like to have a more direct contact and closer co-operation with the wood users. Few contractors are interested in expanding their business with more logging teams.